2012
DOI: 10.3390/toxins4111343
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR, a Pathway Less Recognized for Staphylococcal Superantigen-Induced Toxicity

Abstract: Immunostimulating staphylococcal enterotoxin B (SEB) and related superantigenic toxins cause diseases in humans and laboratory animals by activating cells of the immune system. These toxins bind directly to the major histocompatibility complex (MHC) class II molecules on antigen-presenting cells and specific Vβ regions of T-cell receptors (TCR), resulting in hyperactivation of both T lymphocytes and monocytes/macrophages. Activated host cells produce excessive amounts of proinflammatory cytokines and chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 144 publications
(202 reference statements)
0
12
0
Order By: Relevance
“…In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref. 53).…”
Section: Discussionmentioning
confidence: 79%
“…In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref. 53).…”
Section: Discussionmentioning
confidence: 79%
“…In our study, the phosphorylation level of JAK1, JAK3, STAT1, STAT3, STAT5A and STAT5B is all decreased dramatically, which indicated TPD7 inhibited JAK/STAT signalling pathway via suppressing the expression of IL‐2R (Figure ). Furthermore, the PI3K/AKT/mTOR signalling pathway can also be activated by IL‐2R, which is relevant to tumour growth, cell survival, cell proliferation, cell cycle progression and apoptosis . In addition, it has been revealed that the essential tumour suppressor gene PTEN encodes a phosphatase protein against the PI3K/AKT anti‐apoptotic pathway .…”
Section: Discussionmentioning
confidence: 99%
“…A description of these signal transduction pathways upon superantigen binding to host cell receptors was presented recently (Figure 1) [70]. Phosphorylation and dephosphorylation events modulate all three cascades with specific kinases and phosphatases.…”
Section: Cross-talk Among Key Signaling Pathwaysmentioning
confidence: 99%